Factors contributing to neck pain in patients with degenerative cervical myelopathy: A prospective multicenter study. (5th April 2022) - Inose, Hiroyuki; Hirai, Takashi; Yoshii, Toshitaka; Kimura, Atsushi; Takeshita, Katsushi; Inoue, Hirokazu; Maekawa, Asato; Endo, Kenji; Miyamoto, Takuya; Furuya, Takeo; Nakamura, Akira; Mori, Kanji; et al.
Purpose: Although the understanding of the mechanisms of low back pain due to spinopelvic sagittal imbalance has strengthened, the understanding of the mechanisms of neck pain remains insufficient. Thus, this study aimed to identify the factors associated with preoperative and postoperative neck pain in patients with degenerative cervical myelopathy who underwent laminoplasty. Methods: In this prospective multicenter study, we prospectively enrolled patients who were scheduled for laminoplasty for degenerative cervical myelopathy. The associations between different variables and the Numerical Pain Rating Scale (NRS) scores for neck pain were investigated using univariate and multiple linear regression models. Results: In total, 92 patients were included in the current study. The univariate analysis showed that age, sex, cervical lordosis in neutral and extension, and thoracic kyphosis were significantly associated with the preoperative NRS score for neck pain; moreover, preoperative cervical lordosis in extension and range of motion and postoperative cervical lordosis in neutral, flexion, and extension were significantly associated with the postoperative NRS Scale score for neck pain. Stepwise multiple regression analysis showed that the independent factors contributing to preoperative neck pain were preoperative cervical lordosis in extension, sex, and age. The independent preoperative predictor and contributor to postoperative neck pain were preoperative cervical lordosis in extension and postoperative cervical lordosis in extension, respectively. Conclusions: Cervical lordosis in extension showed significant association with neck pain in patients with degenerative cervical myelopathy. Therefore, when performing laminoplasty for patients with a low cervical lordosis in extension, attention should be paid to residual postoperative neck pain.